2006
DOI: 10.1074/jbc.m508445200
|View full text |Cite
|
Sign up to set email alerts
|

A Dominant Role for FE65 (APBB1) in Nuclear Signaling

Abstract: FE65 has been described as an adaptor protein; its partners include the ␤-amyloid precursor protein (APP) and Tip60 (a histone acetyltransferase). Recent evidence suggests that APP may function in a nuclear signaling pathway via formation of APP-FE65-Tip60 complexes. The evidence is largely based on experiments in which APP/Tip60 is fused to the DNA binding domain of a yeast transcriptional factor Gal4 (Gal4DB) that can activate a reporter gene only when FE65 is coexpressed. One interpretation of published exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 50 publications
3
41
0
Order By: Relevance
“…g-secretase cleavage then releases Fe65 together with AICD, thereby allowing Fe65 to enter the nucleus and to interact with Tip60 (Cao and Südhof 2004); (2) Hass and Yankner revealed that PS-dependent AICD production is not required for the APP signaling activity as it proceeds normally in PS null cells and on PS inhibitor treatment (Hass and Yankner 2005). Instead, the investigators provided an alternative pathway involving Tip60 phosphorylation; (3) a later report documented that the proposed signaling activity is, in fact, executed by Fe65 independently of APP (Yang et al 2006). Last, the link of Fe65 to chromatin remodeling instead of transcription suggests that APP may not act on specific genes, but rather modulates the overall transcriptional state of a cell (Giliberto et al 2008).…”
Section: Intracellular Signalingmentioning
confidence: 99%
“…g-secretase cleavage then releases Fe65 together with AICD, thereby allowing Fe65 to enter the nucleus and to interact with Tip60 (Cao and Südhof 2004); (2) Hass and Yankner revealed that PS-dependent AICD production is not required for the APP signaling activity as it proceeds normally in PS null cells and on PS inhibitor treatment (Hass and Yankner 2005). Instead, the investigators provided an alternative pathway involving Tip60 phosphorylation; (3) a later report documented that the proposed signaling activity is, in fact, executed by Fe65 independently of APP (Yang et al 2006). Last, the link of Fe65 to chromatin remodeling instead of transcription suggests that APP may not act on specific genes, but rather modulates the overall transcriptional state of a cell (Giliberto et al 2008).…”
Section: Intracellular Signalingmentioning
confidence: 99%
“…However, the identification of several putative target genes have been controversially discussed (Baek et al, 2002;Bimonte et al, 2004;Müller et al, 2007;Telese et al, 2005;von Rotz et al, 2004). Elucidation of the role of FE65 in a gene expression complex is further complicated by the observation that FE65 itself triggers robust gene expression in a reporter assay (Yang et al, 2006). Microscopy studies revealed that the above described complex consisting of AICD, FE65 and TIP60, is visible as speckles in the nucleus (Muresan and Muresan, 2004;von Rotz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The AICD contains a conserved YENPTY motif that enables interaction with a number of binding proteins via their phosphotyrosine-binding domain, for example with Fe65, JNK interacting protein ( JIP1) and ShC proteins (De Strooper & Annaert 2000). In particular, the APP adaptor protein Fe65 is involved in nuclear signalling of APP and in cell damage response (von Rotz et al 2004, Yang et al 2006. In addition, APP has been linked to the pro-apoptotic JNK pathway via JIP1 (Matsuda et al 2001, Taru et al 2002b.…”
Section: Introductionmentioning
confidence: 99%